Analysis of Service Quality on Building Loyalty by Using Structural Equation Modelling Method (Case Study in Majapahit Railways) - Eka Arista Anggorowati (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2015)
Train system is one of the transportation modes with some special characteristics that make it becomes an effective and efficient transportation system to increase the service quality. Although the AC economy class of Majapahit Railway has been officially opened by the government, it has not been able to fulfill the people’s need. It is proved with the decrease of number of passenger, and the increase of critics related to the service quality. This research aims to analyze the principal elements and the effect of service qualities towards the customer’s loyalty. The research was conducted through survey on the Majapahit railway users consisting of 200 respondents. The used sampling technique was non probability sampling with purposive sampling method. It applied Structural Equation Modelling in which the previous test was the classical assumptions. Based on the calculations, it is indicated that the variables of service quality in customer satisfaction and loyalty is significant. The principal elements that influence satisfaction and loyalty are the operational schedule, the rolling stock condition, station’s comfort and security, safety, ticket price, and how the passengers enjoy the travelling. Adjusted R square of 0.8246 shows that 82 percent of consumer’ loyalty can give impact on service quality and customer satisfaction.